Single-step sintering of zirconia ceramics using hydroxide precursors and Spark Plasma Sintering below 400 °C. (15th July 2019) - Elissalde, C.; Chung, U-C.; Josse, M.; Goglio, G.; Suchomel, M.R.; Majimel, J.; Weibel, A.; Soubie, F.; Flaureau, A.; Fregeac, A.; Estournès, C.
Abstract: The densification of zirconia at very low temperatures (<400 °C) requires enhanced synergy between thermodynamics and kinetics. This work demonstrates an efficient single step approach combining amorphous hydrated zirconia and Spark Plasma Sintering at 350 °C and 600 MPa. The resulting zirconia ceramics exhibit a cohesive nanostructure with small average grain sizes (20 nm) and a predominantly monoclinic structural polymorph confirmed by both X-ray scattering analyses and High Resolution Transmission Electronic Microscopy. Remarkable Vickers hardness of 3.8 GPa for high level of porosity (30%) is explained by the density and homogeneous distribution of grains boundaries and meso /microporosities. Graphical abstract: Unlabelled Image